An association between gestational diabetes mellitus and long-term maternal cardiovascular morbidity. Issue 15 (8th June 2013) - Kessous, Roy; Shoham-Vardi, Ilana; Pariente, Gali; Sherf, Michael; Sheiner, Eyal
Abstract : Objective: To investigate whether a diagnosis of gestational diabetes mellitus (GDM) is a risk factor for subsequent long-term cardiovascular morbidity. Design: A population-based study. Setting: Soroka University Medical Center, a tertiary centre in the southern region of Israel. Patients: A cohort of women with and without a diagnosis of GDM who delivered during the years 1988–1999 with a follow-up period until 2010. Interventions: A comparison of the incidence of cardiovascular morbidity. Results: Of 47 909 deliveries that met the inclusion criteria, 4928 (10.3%) occurred in patients who were diagnosed with GDM. During a follow-up period of more than 10 years, compared with women who gave birth at the same time period, after adjustment for age and ethnicity, patients with GDM had higher rates of cardiovascular morbidity including non-invasive cardiac diagnostic procedures (OR=1.8; 95% CI 1.4 to 2.2), simple cardiovascular events (OR=2.7; 95% CI 2.4 to 3.1) and total cardiovascular hospitalisations (OR=2.3; 95% CI 2.0 to 2.5). In a Cox proportional hazards model, adjusted for comorbidities such as pre-eclampsia and obesity, GDM was independently associated with cardiovascular hospitalisations (adjusted HR 2.6, 95% CI 2.3 to 3). Conclusions: GDM is an independent risk factor for long-term cardiovascular morbidity in a follow-up period of more than a decade.